Implementation of primary nursing at Pediatric Department, Azienda Ospedaliera SS Antonio e Biagio e Cesare Arrigo, Alessandria, Italy (Working Paper of Public Health, 2021)
Introduction: The principles of assistance that consider man in his entirety also apply to the child but the differences with respect to adult assistance lie in the specific needs of the child, in his dependence and capacity for development. One cannot think of the child without the parents; the whole family is involved in the care plan and in particular the parents must have an active role within the care plan.Methods: The pediatric nurse has two interlocutors and therefore must adopt two different modes of communication: parents and children, both of which must be taken care of. In this regard, the functional care model is no longer responsive to the needs of personalized care, the need to find new strategies to respond to the health needs of the child, has directed the nursing management of the Alessandria Hospital towards the project of implementation of the Primary Nursing model at the Complex Structure of Pediatrics.Results: Completion of the experimental implementation period on time. User customer satisfaction will be assessed through the questionnaires already in use at the company. Staff satisfaction will be assessed through the monitoring of indicators such as continuous feedback between staff, project representative and Coordinator, active participation in team meetings, suggestions and proposals by nurses about the management of critical issues and improvement. Any periods of absence and transfer requests will also be monitored. A Pre-post research study is also planned on the impact of Primary Nursing on the nursing team and on patients and their families.Conclusions: Overall, patients, families, and nurses value care continuity and meaningful nurse-patient relationships, which is fundamental to primary nursing.